Knowledge of Student’s Understanding and The Effect on Instructional Strategies: a Case of Two Novice Mathematics Teachers - Masduki, Masduki; Suwarsono, Stephanus; Budiarto, Mega Teguh (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2017)
Pedagogical content knowledge plays a role in learning in classroom. The study aims to 1) analyze the teachers’ knowledge of the students' errors and difficulties in solving linear equations and 2) describe the instructional strategies used by teachers to reduce their errors and difficulties. The subjects were two novice teachers who have taught the Junior High School 7th grade students with different math abilities for two years. The data collection was conducted by open questionnaire and interview. The results showed that both teachers have knowledge of students' errors and difficulties in solving linear equations. However, the teacher's learning strategies in helping students reduce students' errors and difficulties were different from one another. It can be concluded that the teacher's knowledge of the students’ errors and difficulties can help teachers determine the appropriate learning strategies to present a learning subject matter.